Assessment of symptoms in COMET-ICE, a phase 2/3 study of sotrovimab for early treatment of non-hospitalized patients with COVID-19 - Sacha Satram; Parima Ghafoori; Carolina M. Reyes; Tom J. H. Keeley; Helen J. Birch; Dimitra Brintziki; Melissa Aldinger; Elizabeth Alexander; Amanda Lopuski; Elias H. Sarkis; Anil Gupta; Adrienne E. Shapiro; et al. (SpringerOpen, 2023)
Abstract Background The COMET-ICE trial demonstrated that sotrovimab clinically and statistically significantly reduces the risk of all-cause > 24-h hospitalization or death due to any cause among patients with COVID-19 at high risk of disease progression. Patient-reported outcomes are important to capture symptom burden of COVID-19 and assess treatment effectiveness. This study investigated symptoms and their impact over the acute phase of COVID-19 infection among patients on sotrovimab versus placebo. Methods Randomized (1:1), double-blind, multicenter, placebo-controlled, phase 2/3 study in 57 centers across five countries. Participants were non-hospitalized patients with symptomatic, mild-to-moderate COVID-19 and ≥ 1 baseline risk factor for disease progression (aged ≥ 55 years or ≥ 1 of the following: diabetes requiring medication, obesity, chronic kidney disease, congestive heart failure, chronic obstructive pulmonary disease, or moderate-to-severe asthma). An intravenous infusion of sotrovimab 500 mg or placebo was administered on Day 1. The FLU-PRO Plus questionnaire was administered once-daily with 24-h recall from Day 1-21, and at Day 29. Intensity and duration of COVID-19 symptoms were determined from area under the curve (AUC) and mean change in total and individual domain scores through Days 7, 14, and 21. Time to symptom alleviation was assessed. Results In total, 1057 patients were randomized to sotrovimab (n = 528) or placebo (n = 529). At Day 7, mean decrease in FLU-PRO Plus total score (measured by AUC) was statistically significantly greater for patients on sotrovimab (-3.05 [95% confidence interval (CI) -3.27 to -2.83]) than placebo (-1.98 [95% CI -2.20 to -1.76]; difference -1.07 [95% CI -1.38 to -0.76]; p < 0.001). Significant differences were also observed at Days 14 and 21. A more rapid decline in symptom severity was observed with sotrovimab versus placebo through Week 1 and the first 21 days post-treatment. By Day 21, 41% of patients on sotrovimab and 34% on placebo reported symptom resolution. In a post-hoc analysis, median time to symptom alleviation was 4 and 6 days, respectively. Conclusions Sotrovimab provides significant and rapid improvements in patient-reported COVID-19 symptoms, as measured by the FLU-PRO Plus. These results further show the benefits of sotrovimab in alleviating symptoms among high-risk patients with COVID-19. Trial registration ClinicalTrials.Gov: NCT04545060 ( https://clinicaltrials.gov/ct2/show/NCT04545060 ). Date of registration: September 10, 2020 (retrospectively registered).